Amperometric environmental phosphate sensor - Lu, Y; Li, X; Li, D; Compton, R (American Chemical Society, 2021)
We report a novel amperometric sensor for aqueous phosphate ions in freshwater systems based on the reductive square wave voltammetry of molybdate (VI) anions immobilized within a chitosan matrix deposited on a glassy carbon electrode. A sensitivity of 4.4±0.1 μA/μM was realized together with a LOD of 0.15 μM. The sensor was insensitive to chloride and nitrate ions below threshold concentration of 1.0 mM respectively. Analytical measurements were successfully made in authentic samples of tap and pond water.